Experiment and Modeling of Water Vapour Decomposition on ZrNi5 Alloy - Yao, Yong; Luo, Deli; Huang, Zhiyong; Song, Jiangfeng (Asian Journal of Chemistry, 2013)
In order to simulate tritium recovery from tritiated water by hot metal bed.ZrNi5 powder was used to decompose water vapour in inert gas argon. Kinetics of the reaction was studied by thermogravimetric analyzer, the reaction mechanism at 723 K could be described by first-order chemical reaction. One-dimensional quasi-homogenous model was built to predict the breakthrough performance of the fixed bed reactor, the model integrated with kinetics parameter was solved by comsol multiphysics. The predicted breakthrough curves were compared with experiment data, it was shown that the modeling results agree well with experiment.